Physicochemical characterization and content of lactic acid bacteria of cheese “Paria” from Arequipa, Peru - Díaz-García, Angela C. (2020)
Cheese “paria” is a semi-hard matured cheese, produced mainly in Puno, Arequipa and Cusco, Peru. At present, it has great export potential, however, it still lacks complete quality parameters. The objectives of this research were to evaluate the physicochemical characteristics and the content of lactic acid bacteria (LAB) of three brands of cheese “paria”, from Arequipa (Peru). The physicochemical parameters evaluated were pH, moisture, total solids (TS), water activity (aw), sodium chloride (NaCl), fat and protein. The brands of “paria” cheese presented organoleptic characteristics similar to those reported in the Peruvian technical standards, and physicochemical values were; pH from 5.15 to 6.11; moisture from 42.94 to 45.33 g%; TS from 54.67 to 57.06 g%; aw from 0.928 to 0.958; NaCl from 1.74 to 3.07 g%; fat from 27.33 to 31.0 g% and protein from 20.58 to 23.41 g%. The BAL content varied from 8.06 to 8.56 Log cfu/g. Significant differences were found between the brands for pH, aw, NaCl, fat, and BAL counts. A direct correlation of BAL content with NaCl content was presented, while an inverse correlation with pH and fat content was presented; therefore, these physicochemical parameters can be used for indirect control of the BAL content in the cheeses studied.